Weed biocontrol with fungi: past, present and future. Issue 10 (2nd October 2016) - Hershenhorn, Joseph; Casella, Francesca; Vurro, Maurizio
ABSTRACT: The idea of using living organisms for weed control goes back over a century, and very encouraging results were obtained from the 1960s to the 1970s. It is foreseeable and desirable that in the near future, further reasons will support the development and financial sustainment of this research field. The authors describe past and present successes, and discuss possible approaches for improving future achievements.